Membentuk Generasi Muda yang Tangguh dalam Menghadapi Dampak Negatif Pinjaman Online melalui Pendidikan Pancasila di Era Society 5.0 - Edy Sofyan (Departement of Mathematics Education, 2023)
Amidst the age of globalisation, the younger cohort confronts the adverse repercussions of online loans, necessitating a prudent strategy for managing them. The implementation of Pancasila education has been recognised as a viable approach to cultivate a resilient younger generation capable of confronting the adverse consequences of the Society 5.0 era. The study emphasises the significance of character education in the execution of policies, as it can establish a solid basis for the younger generation to confront these difficulties. Moreover, research indicates that internet gambling is a societal issue with a substantial adverse influence, particularly on the younger demographic. The negative consequences encompass the propensity of the younger cohort to exhibit indolence in their professional endeavours, as well as the diversion of financial resources that ought to be allocated towards progress, instead being channelled into gaming activities. This highlights the necessity of moral education, as imparted through Pancasila, in cultivating responsible and ethical individuals in financial management. In addition, the incorporation of ethical principles demonstrates that Pancasila education might facilitate the cultivation of empathy and altruism among the younger population. Therefore, Pancasila education plays a crucial role in shaping a resilient and accountable younger generation in confronting the adverse effects of online loans in the Society 5.0 era.